2022
DOI: 10.1186/s40824-022-00324-z
|View full text |Cite
|
Sign up to set email alerts
|

A functional neuron maturation device provides convenient application on microelectrode array for neural network measurement

Abstract: Background Microelectrode array (MEA) systems are valuable for in vitro assessment of neurotoxicity and drug efficiency. However, several difficulties such as protracted functional maturation and high experimental costs hinder the use of MEA analysis requiring human induced pluripotent stem cells (hiPSCs). Neural network functional parameters are also needed for in vitro to in vivo extrapolation. Methods In the present study, we produced a cost eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…It has been reported that the development of ultra-sensitive neurotransmitter biosensors with sensitivity at the levels of ≤ nano units is meaningful for early disease diagnosis and monitoring [ 15 , 16 , 17 , 18 , 19 ]. In this context, the fusion of biosensors and biomaterials enhances the potential for sensing specific biomolecules [ 20 , 21 , 22 , 23 , 24 , 25 ]. In particular, biocompatible molecules, such as DNA- and RNA-based nucleic acids, are highly beneficial for the sensitive and selective detection of analytes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the development of ultra-sensitive neurotransmitter biosensors with sensitivity at the levels of ≤ nano units is meaningful for early disease diagnosis and monitoring [ 15 , 16 , 17 , 18 , 19 ]. In this context, the fusion of biosensors and biomaterials enhances the potential for sensing specific biomolecules [ 20 , 21 , 22 , 23 , 24 , 25 ]. In particular, biocompatible molecules, such as DNA- and RNA-based nucleic acids, are highly beneficial for the sensitive and selective detection of analytes.…”
Section: Introductionmentioning
confidence: 99%
“…These materials need to possess mechanical properties and biochemical cues that support the functional maturation of 3D neuronal networks [14,15]. Consequently, there is a need for a material that can support long-term cultures, especially those based on 3D neuronal networks derived from h-iPSCs, as achieving functional maturation of induced neurons (iNeurons) in 3D settings requires a relatively long time (6 weeks or more) [16,17], necessitating thus a stable biomaterial [18]. Hydrogels are widely used biomaterials for mimicking the brain's ECM [19,20].…”
Section: Introductionmentioning
confidence: 99%